Andragogical Transmission: the Secret of National Food Surplus - Adegboyega Jibowo, A. (Obafemi Awolowo University Press, 2013)
The history of agricultural extension as a profession had been subsumed under the overall history of agricultural development in Nigeria. Although a well recognised area of knowledge, the development of extension as an academic discipline has not been strongly pursued as that of some other technical agricultural disciplines. Although continuous research is essential for the advancement of knowledge in technical agriculture, much improved information is available which if applied could lead to production of national food surplus. What is lacking is the adequate transmission to, and application of such information by farmers to generate food surplus. However, extension is faced with many problems which had made it ineffective in playing the role of transmitting improved technical information in agriculture to farmers, and assisting them in applying the same. The most important problems include lack of access to adequate financial assistance, inadequate number of extension agents and inadequate supply of farm inputs.